Extraction of lithium from primary and secondary sources by pre-treatment, leaching and separation: A comprehensive review - Meshram P.; Pandey B.D.; Mankhand T.R. (My University, 2025)
In this comprehensive review resources of lithium and status of different processes/technologies in vogue or being developed for extraction of lithium and associated metals from both primary and secondary resources are summarized. Lithium extraction from primary resources such as ores/minerals (spodumene, petalite and lepidolite) by acid, alkaline and chlorination processes and from brines by adsorption, precipitation and ion exchange processes, is critically examined. Problems associated with the exploitation of other resources such as bitterns and seawater are highlighted. As regards the secondary resources, the industrial processes followed and the newer developments aiming at the recovery of lithium from lithium ion batteries (LIBs) are described in detail. In particular pre-treatment of the spent LIBs, leaching of metals from the cathode material in different acids and separation of lithium and other metals from the leach liquors, are discussed. Although spent LIBs are currently processed to recover cobalt and other base metals but not lithium, there is a good prospect for the recovery of lithium in the coming years. Varying compositions of batteries for different applications require development of a suitable recycling process to recover metals from all types of LIBs. © 2014 Elsevier B.V. All rights reserved.